Problematics of Termination of Employment Relations for Workers Undergoing Industrial Relations Trial Period - Arrifqi, Moh Fahmi; Rusdiana, Emmilia; Kusuma, Dinda Puteri Fathurachmah (NOVUM : JURNAL HUKUM, 2025)
Termination of employment (PHK) must be carried out according to legal procedures, beginning with an official termination letter. However, issues may arise when such termination contradicts labor regulations. This research discusses the case of Bunari, a worker who received a termination letter during the trial process, which is suspected to conflict with Article 155 paragraph (2) of the Manpower Law. The main legal issue examined is the ambiguity of norms regarding the validity of termination during ongoing industrial relations disputes. The objective of this study is to analyze the legal validity of the termination letter issued to Bunari during the trial process, as reflected in Decision Number 1237 K/Pdt.Sus-PHI/2017, and to examine the rules surrounding process wages for workers under trial. This study applies a normative juridical method, analyzing legal events using statutory and regulatory frameworks. The findings reveal that the termination of Bunari is not legally valid due to the ongoing industrial dispute process at the time of termination, rendering the letter formally and legally flawed. Furthermore, Bunari is entitled to process wages as he fulfills the required legal elements. Based on Supreme Court Circular Letter (SEMA) No. 3 of 2015, the payment period for process wages is limited to six months. The study recommends reinforcing clarity in regulations regarding termination procedures during legal proceedings and urges employers to strictly adhere to legal mechanisms to prevent arbitrary dismissals and ensure workers' rights are protected.